2022
DOI: 10.2147/idr.s365179
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Vaccination Against SARS-CoV-2 Virus on the Outcome of COVID-19 Disease

Abstract: Background Coronavirus disease 2019 (COVID-19) is a rapidly spreading infection that is on the rise. New variants are continuously appearing with variable degrees of lethality and infectivity. The extensive work since the start of the pandemic has led to the evolution of COVID-19 vaccines with varying mechanisms. We aim to determine real-world data by looking at the different clinical outcomes associated with COVID-19 vaccination, focusing on the rate of hospitalization, severity, and mortality. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…Moreover, the current study revealed that vaccinated persons were less likely to be infected (20%) with COVID19 than nonvaccinated (62.7%). This result was consistent with a study conducted by Moghadas et al, and concluded that there is a 50% reduction of getting infection with COVID-19 after getting the vaccine [29] Also, a study conducted by ALKhafaji et al in Saudi Arabia, reported that the majority of unvaccinated individuals (82.2%) had a higher risk of a critical course of the disease [36].…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the current study revealed that vaccinated persons were less likely to be infected (20%) with COVID19 than nonvaccinated (62.7%). This result was consistent with a study conducted by Moghadas et al, and concluded that there is a 50% reduction of getting infection with COVID-19 after getting the vaccine [29] Also, a study conducted by ALKhafaji et al in Saudi Arabia, reported that the majority of unvaccinated individuals (82.2%) had a higher risk of a critical course of the disease [36].…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the current study revealed that vaccinated persons were less likely to be infected (20%) with COVID19 than nonvaccinated (62.7%). This result was consistent with a study conducted by Moghadas et al, and concluded that there is a 50% reduction of getting infection with COVID-19 after getting the vaccine [29] Also, a study conducted by ALKhafaji et al in Saudi Arabia, reported that the majority of unvaccinated individuals (82.2%) had a higher risk of a critical course of the disease [36].…”
Section: Discussionsupporting
confidence: 89%
“…In Saudi Arabia, COVID-19 case numbers and COVID-19–associated deaths were significantly reduced after introducing BNT162b2 and ChAdOx1-S vaccines [ 26 ]. Other studies in Saudi Arabia reported reduced risk of hospitalization or death for those vaccinated with BNT162b2 or ChAdOx1-S vaccines versus unvaccinated individuals [ 27 , 28 ]. In Qatar, vaccination with both mRNA vaccines were highly protective against COVID-19–related hospitalization or death [ 29 ].…”
Section: Lessons Learned From Primary and Booster Implementationmentioning
confidence: 99%